The effect of children´s disability and long-term illness on parent´s income - Elísabet Eggertsdóttir 1979- (2016)
Objectives: We aim to study the effects of having a severely ill or disabled child on the parent´s finances. Firstly, we examine how the onset of a child’s illness or disability affects the parent´s income. Secondly, we show how income progresses following a period of caring for an ill or disabled child. The broader objective is to examine to what extent parents adapt and if social services meet the needs of individuals who face these circumstances. Data and Methods: Data from Statistics Iceland and The Icelandic Social Insurance Administration is merged on personal identification numbers for the purposes of this study. The treatment group includes beneficiaries who temporarily received home-care allowance during the period from 1997 to 2011. Those treated are matched with up to four control observations on gender, age, pre-treatment income level, marital status and number of dependent children. Generalized least square regression with random effects is used for the statistical examination. Results: The treatment group has a lower average total income than the control group in the time interval of the research. The period of receiving home-care allowance shows the treated group to have higher income than their counterparts. In the period following the termination of the allowance, income for the treated group is however lower than for those untreated. Conclusion and discussion: Although labour-market income is reduced, parents do not appear to face a decrease in total income while receiving home-care allowance. However parents do not adjust well financially after the allowance is terminated. This indicates that parents might need greater support after a period of taking care of an ill or disabled child.